The Integration of The Two-Dimensional Pancasila and The Transcendental Values of The Qur’an as A Philosophical Roadmap Towards Golden Indonesia 2045 - Linda Novianti (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
This research is motivated by the realisation that Indonesia is currently navigating a crucial phase on the path to ‘Golden Indonesia 2045’, a pivotal moment that demands not only material progress but also the strengthening of the nation’s ideology, morality and spirituality. Pancasila, as the philosophical foundation of the state, faces serious challenges in practice, where its values are often reduced to mere formal symbols lacking any real transformative power. In this context, the two-dimensional integration of Pancasila with the transcendental values of the Qur’an is viewed as urgent, serving as a philosophical roadmap to guide national development that is just, civilised, and dignified. Qur’anic values such as tawhid, justice, brotherhood, consultation, and trustworthiness provide an ethical-spiritual foundation that is in harmony with the principles of Pancasila, whilst also serving as a pillar in responding to the challenges of globalisation, technological disruption, and moral crisis. The research method employed is qualitative, utilising a library research approach, through the examination of primary and secondary literature comprising the Qur’an and relevant academic studies. Research findings indicate that the integration of the two-dimensional principles of Pancasila and the transcendental values of the Qur’an can strengthen national practice, making Pancasila not merely a political consensus, but also a robust ethical and spiritual guide. This philosophical roadmap guides national development towards Golden Indonesia 2045 so that it is not solely oriented towards economic growth, but also towards the formation of outstanding, just, principled, religious, and globally competitive Indonesian citizens.